2014
DOI: 10.1002/cncr.28858
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of metastatic medullary thyroid cancer

Abstract: Medullary thyroid cancer (MTC) is an aggressive form of thyroid cancer, which occurs in both heritable and sporadic forms. Discovery that mutations in the RET protooncogene predispose to familial cases of this disease has allowed for presymptomatic identification of gene carriers and prophylactic surgery to improve the prognosis of these patients. A significant number of patients with the sporadic type of MTC and even with familial disease, still present with nodal or distant metastases, making surgical cure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 137 publications
(345 reference statements)
0
43
0
Order By: Relevance
“…MTC is a slow-growing cancer, and even the 10-year overall survival rate is 40-50% in the presence of metastatic disease. Surgery is the only curative modality available [39], and no effective therapies exist for metastatic MTC, as it is not responsive to external radiotherapy, radionuclide therapy or chemotherapy.…”
Section: Molecular Pathways In Mtcmentioning
confidence: 99%
“…MTC is a slow-growing cancer, and even the 10-year overall survival rate is 40-50% in the presence of metastatic disease. Surgery is the only curative modality available [39], and no effective therapies exist for metastatic MTC, as it is not responsive to external radiotherapy, radionuclide therapy or chemotherapy.…”
Section: Molecular Pathways In Mtcmentioning
confidence: 99%
“…There is a tendency to spread quickly to locoregional lymph nodes at presentation that makes early definitive surgery P a g e | 24 difficult. A total thyroidectomy and lymphadenectomy will result in biochemical remission and cure in 40% of cases 21 . MTC is derived from the C cells of the thyroid follicle, which represents a variant of a neuroendocrine cell that produces calcitonin and does not concentrate iodine.…”
Section: Recurrence/relapsementioning
confidence: 99%
“…A previous study indicated that the thyroid cancer incidence rate in Canada was the fastest increasing rate in the world, t trends in the incidence rate of thyroid cancer have demonstrated a 6.8% increase for males and 6.9% increase for females per annum between 1998 and 2007 (16)(17)(18). Most recently, the number of new cases of thyroid cancer is estimated to be 12.9 per 100,000 men and women annually in 2015 in the US (19,20).…”
Section: Introductionmentioning
confidence: 98%
“…At present, previous studies (17,19,21) have suggested that gene therapy is the most promising and effective therapeutic method for thyroid cancer. The principle of gene therapy depends on the intracellular conversion of a relatively non-toxic pro-drug (or drug gene) to a toxic drug (therapeutic protein) through gene transcription and translation processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation